2006
DOI: 10.1200/jco.2006.06.4964
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Depsipeptide in Pediatric Patients With Refractory Solid Tumors: A Children's Oncology Group Report

Abstract: Depsipeptide is well tolerated in children with recurrent or refractory solid tumors when administered weekly for 3 consecutive weeks every 28 days and inhibits histone deacetylase activity in PBMC in a dose-independent manner. The recommended phase II dose in children with solid tumors is 17 mg/m2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 30 publications
(5 reference statements)
3
50
1
Order By: Relevance
“…As shown in Table 3 results), romidepsin significantly increased the surface expression of CD20 on Burkitt lymphoma and B104 cells at 5-10 nM, which were far lower than the maximum plasma concentration determined in phase I clinical trials (1.0-1.4 mM). [36][37][38] Romidepsin also had remarkable cytotoxic activities at the same concentrations (Supplementary Figure S2 and Table S2), consistent with the notion that this drug is one of the most effective HDAC inhibitors against hematological malignancies both in vitro and in vivo. 39,40 The upregulation of CD20 was not generalized to other B-cell-specific antigens, as the expression levels of CD10, CD21, CD43 and CD44 did not change in response to HDAC inhibitors (data not shown).…”
Section: Hdac Inhibitors Enhance the Expression Of Cd20 Antigen On B-supporting
confidence: 66%
See 1 more Smart Citation
“…As shown in Table 3 results), romidepsin significantly increased the surface expression of CD20 on Burkitt lymphoma and B104 cells at 5-10 nM, which were far lower than the maximum plasma concentration determined in phase I clinical trials (1.0-1.4 mM). [36][37][38] Romidepsin also had remarkable cytotoxic activities at the same concentrations (Supplementary Figure S2 and Table S2), consistent with the notion that this drug is one of the most effective HDAC inhibitors against hematological malignancies both in vitro and in vivo. 39,40 The upregulation of CD20 was not generalized to other B-cell-specific antigens, as the expression levels of CD10, CD21, CD43 and CD44 did not change in response to HDAC inhibitors (data not shown).…”
Section: Hdac Inhibitors Enhance the Expression Of Cd20 Antigen On B-supporting
confidence: 66%
“…16,40 However, recent clinical trials concluded that HDAC inhibitors had only limited clinical activity when used as monotherapy. 33,34,[36][37][38] Our present study suggests a more effective way of their application; the ability of HDAC inhibitors to modify the expression of surface molecules may provide a new avenue for the clinical application of HDAC inhibitors, for example, as immunopotentiators or chemosensitizers. Hence, the combination with HDAC inhibitors not only enhances anti-lymphoma activity, but also expands the clinical utility of rituximab for other disorders, such as autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The disposition of romidepsin has been shown to follow a polyexponential decline with a linear elimination and has been described by a 2-compartment pharmacokinetic (PK) model. No apparent nonlinearity has been reported for romidepsin disposition within the range of 1 to 24.9 mg/m 2 (7,8) The PK of romidepsin does not seem to be affected by repeated dosing. The most extensive clinical PK analysis was done recently by Woo and colleagues (9), in which 98 patients were enrolled in a phase II.…”
Section: Romidepsin Metabolism and Pharmacokineticsmentioning
confidence: 99%
“…There have been multiple phase I trials with romidepsin in patients with refractory solid tumors (7,8), chronic leukemia, myeloma (10), acute myeloid leukemia (11), and T-cell lymphoma. The maximum-tolerated dose was established at 17 to 18 mg/m 2 infused over 4 hours on day 1 and day 5 of a 21-day cycle and 13.3 mg on days 1, 8, and 15 of a 28-day cycle.…”
Section: Early Clinical Studies Of Romidepsinmentioning
confidence: 99%
“…23 A preclinical study in rats showed that 66% of the dose was excreted into the bile, mediated via the ATP-binding cassette transporter ABCB 1(P-glycoprotein, MDR1), for which romidepsin has been identified as a substrate. 24 Romidepsin is also likely to be a substrate of the organic transporter, OATP1B3, an influx transporter encoded by SLCO1B3, because other cyclic peptides have been shown to interact with the same transporter.…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 99%